Highly conductive graphenated-carbon nanotubes sheet with graphene foliates for counter electrode application in dye- sensitized solar cells - Yusuf, Yusnita; Shafie, Suhaidi; Ismail, Ismayadi; Ahmad, Fauzan; Hamidon, Mohd Nizar; Sudhir, Pandey Shyam; Wei, Lei (Universiti Putra Malaysia, 2023)
This work enlightened the synthesis of graphenated-carbon nanotubes sheet (g-CNT) using the floating-catalyst chemical vapor deposition method (FCCVD) for dye-sensitized solar cell (DSSC) application. The carbon injection flow rate in the experiment was varied to 6, 8, and 10 ml/h. The morphological findings revealed that the g-CNT formed a highly conductive network. Excellent conductivity was obtained for the sample g-CNT8 (34.5 S/cm) compared to the sample g-CNT6 (11.2S/cm) and CNT10 (4.76 S/cm). This excellent feature is due to the hybrid structure of the g-CNT8, which creates efficient electron transfer in the materials resulting in higher conductivity. The hybrid structure provides a high surface area that improves conductivity. Therefore, the g-CNT sheet is an excellent candidate to replace the conventional platinum used as a counter electrode (CE) in DSSC.